2012
DOI: 10.1002/jso.23297
|View full text |Cite
|
Sign up to set email alerts
|

Malignant pheochromocytoma and paraganglioma: A population level analysis of long‐term survival over two decades

Abstract: Malignant PHEO has a more aggressive course than malignant PGL; long-term survival has not improved over the last two decades. Multi-institutional efforts should be pursued to seek novel treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 19 publications
7
64
0
1
Order By: Relevance
“…We initially attributed this to the selected cut-off (5.5 cm), which was more representative of the size of primary PGLs (and divided them almost evenly) and divided the PHEOs quite unevenly. However, when we used 8 cm as a cutoff, the median size of PHEO primary tumors, there was again no survival difference in PHEOs between those with small vs. large tumors (P = 0.81) Significantly larger tumors in patients with PHEO than with PGL have been reported previously [24]. …”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We initially attributed this to the selected cut-off (5.5 cm), which was more representative of the size of primary PGLs (and divided them almost evenly) and divided the PHEOs quite unevenly. However, when we used 8 cm as a cutoff, the median size of PHEO primary tumors, there was again no survival difference in PHEOs between those with small vs. large tumors (P = 0.81) Significantly larger tumors in patients with PHEO than with PGL have been reported previously [24]. …”
Section: Discussionmentioning
confidence: 61%
“…A previous study, which did not classify the tumors based on genetic background, found overall survival to be significantly shorter in patients with PGLs than with PHEOs [19]. A different study, which also did not consider the genetic background of the disease and included only metastatic PHEO/PGL, reported better survival of PGLs [24]. Our study, including only patients with SDHB -related tumors, found that patients with PGLs had a better overall survival than patients with PHEOs.…”
Section: Discussionmentioning
confidence: 99%
“…So far, 16 genes are known to be associated with PCCs/PGLs: SDHA, SDHB, SDHC, SDHD and SDHAF2 (together SDHx), VHL, RET, NF1, TMEM127, MAX, KIF1B, and PHD2, as well as the recently identified HIF2A (2, 4, 5, 6), HRAS (7), FH (8), and PHD1 (9). The identification of distant metastases is still the only proof of malignancy in PCCs/PGLs, and because treatment options are limited, finding an appropriate strategy poses a clinical challenge (10). A better mechanistic understanding of tumorigenesis, proliferation, and malignant behavior is therefore warranted.…”
Section: Introductionmentioning
confidence: 99%
“…We describe the demographic, clinical, and pathologic characteristics of A previous population-based study of 287 malignant pheochromocytomas diagnosed between 1988 and 2008 in the surveillance, epidemiology, and end results (SEER) database investigated predictors of overall mortality [25]. The 5-year overall survival rate was 58.1 %; presentation at diagnosis with distant metastases and failure to undergo surgery were factors independently associated with compromised survival.…”
Section: Discussionmentioning
confidence: 99%